Evaluation of Anti-E6 Single Domain Antibodies for the Treatment of Human Papillomavirus-related Cancer - Faulkner, Ashley (My University, 2022)
The HPV16 genome encodes two oncoproteins, E6 and E7, which are essential for viral carcinogenesis. While E7 promotes cell proliferation, E6 abolishes the resulting p53-dependent apoptotic response. We hypothesized that antibodies targeting the E6 protein will allow for p53 restoration and induce apoptosis of the infected cells. Our lab has previously generated a pool of 20 Camelidae-derived single-domain antibodies (VHHs) against the E6 protein (Togtema et al. 2019). VHHs have several properties making them well-suited for therapeutic purposes including low immunogenicity, high stability, and capacity to bind epitopes not accessible to any other type of antibody. In the current project, we used dot blots to evaluate the VHHs binding potential to various recombinant E6 proteins, identifying several successful VHH candidates. Co- immunoprecipitation using Affigel resin was used to confirm the VHH’s endogenous E6 binding capacity in CaSki cells. Therein, two clones, C26 and A37, were identified as efficient E6 binders, in triplicate. Interestingly, in denaturing Western Blot analyses, C26 was found to react with the maltose-binding protein (MBP)-containing proteins but not with E6 6C/6S lacking an MBP tag, supporting the hypothesis that C26 binds MBP or E6 through different parts of the antibody. To deliver the VHHs to target cells, cationic lipid-based protein transfection proved inadequate, however mRNA transfection resulted in improved transfection efficiency. Functional assays, including proliferation assays to assess cell proliferation, and immunodetection of p53 and PARP- 1 cleavage following mRNA transfection, were used to evaluate the VHH’s therapeutic potential. Our results indicate that further optimization of our molecules will be needed to yield VHHs with therapeutic potential, however, our methodology may serve as a template for other researchers, creating a pipeline of analysis for the evaluation of antibodies against the E6 protein.